Multi‐Magnetic Properties of a Novel SCO [Fe(3‐OMe‐Sal2trien)][Fe(tdas)2]·CH3CN Salt. Issue 48 (12th November 2020) - Spitsyna, Nataliya; Ovanesyan, Nikolay; Blagov, Maxim; Krapivin, Vladimir; Lobach, Anatolii; Dmitriev, Alexei; Simonov, Sergey; Zorina, Leokadiya; Pilia, Luca; Deplano, Paola; Vasiliev, Alexander; Maximova, Olga; et al.
Abstract : The multi‐magnetic salt [Fe(3‐OMe‐Sal2 trien)][Fe(tdas)2 ]· CH3 CN (1 ) has been prepared and fully characterized by a variety of methods. The crystal structure of 1, determined at 150, 297 and 350 K, consists of alternating layers composed by a parallel arrangement of the chains of isolated π–π coupled cation pairs of [Fe(3‐OMe‐Sal2 trien)] + and anion pairs of [Fe(tdas)2 ] – . The complex magnetic behavior of this salt is consistent with the sum of the contributions from spin‐crossover (SCO) cations and strong antiferromagnetically (AFM) coupled dimeric [Fe(tdas)2 ]2 2– anions. The observed gradual thermally induced spin transition ( T 1/2 = 195 K) is relatable to the cation exhibiting disordering of ethylene (–CH2 –CH2 –) groups between two conformers with a narrow thermal hysteresis of 6 K. The dc magnetization measurements and 57 Fe Mössbauer spectroscopy at room temperature are in excellent agreement between γ HS (%) value and ratio of disordering of ethylene groups obtained from X‐ray analysis. Mössbauer spectra at 80 K and 296 K indicate a spin transition between S = 1/2 and S = 5/2 for the iron(III) saltrien‐cation and confirms S = 3/2 for the [Fe III (tdas)2 ] – anion. The experimental results are supplemented with a theoretical Density Functional Theory (DFT) analysis. Abstract : The fully characterized multi‐magnetic salt [Fe(3‐OMe‐Sal2 trien)][Fe(tdas)2 ]· CH3 CN shows a gradual thermally induced spin‐crossover along with an antiferromagnetic exchange coupling in dimerized [Fe(tdas)2 ]2 2 – anions.